Volume 2: Mechanics and Behavior of Active Materials; Integrated System Design and Implementation; Bioinspired Smart Materials 2014
DOI: 10.1115/smasis2014-7467
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Shape Memory Alloy Wires in Fiber Reinforced Polymers for Endless Crash Absorber Structures

Abstract: Today in most cases crash absorber elements are made of metals. Those materials absorb the energy during a crash event by ductile plastification, as e.g. by buckling. Fiber reinforced polymers (FRP) offer due to their heterogenic structure several failure mechanisms for energy absorption under compressive load, such as fiber-break, matrix-break, delamination, fiber pull-out, fiber-matrix-interphase failure and friction processes. This in combination with the low density leads to significantly better specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In another study, Wierschem and Andrawes [ 55 ] utilized SMA wires and glass fibers in GFRP composites and showed that SMA wires could improve the ductility of composites. Nissle et al [ 56 ] used super-elastic SMA wires with conventional FRP composites to avoid damage propagation in composites. Sharifi et al [ 57 ] produced a smart FRP composite consisting of two layers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Wierschem and Andrawes [ 55 ] utilized SMA wires and glass fibers in GFRP composites and showed that SMA wires could improve the ductility of composites. Nissle et al [ 56 ] used super-elastic SMA wires with conventional FRP composites to avoid damage propagation in composites. Sharifi et al [ 57 ] produced a smart FRP composite consisting of two layers.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, asymmetric specimens showed very low tensile strength. Pappada et al [ 54 ], Nissle et al [ 56 ], Cohades et al [ 58 ], and Lidan Xu et al [ 59 ] used super-elastic SMA wires with conventional FRP composites to increase their impact resistance and avoid damage propagation in composites. Zafar and Andrawes [ 10 , 14 ] produced SMA-FRP composites using SMA and glass fibers and tested them under uniaxial tensile loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches on designing the SMA hybrid composites (SMAHCs) show the effects of some parameters like volume fraction of SMA, surface treatment , pre‐strain of SMA wires and matrix curing process .Several researchers have investigated the use of SMA wires in fiber‐epoxy composites. Pappada et al and Nissle et al embedded superelastic SMA wires in fiber reinforced polymer composites to avoid propagating of defect in the composite and enhanced mechanical properties such as energy absorption and impact applications.…”
Section: Introductionmentioning
confidence: 99%